The adoption of Intelligent Applications by South African Organisations - Kawal, Chiresh (University of the Witwatersrand, Johannesburg, 2025)
Digital disruption has impacted many industries globally. Not all industries have been equally impacted; some have experienced more disruption than others. The ICT industry, among others, is closest to the centre of the vortex indicating the extent to which it has been disrupted compared to others. Digital technologies are merging to leverage their combined capabilities in forming more powerful tools to aid industries to cope with organisational transformation. This quantitative study uses the extended Unified Theory of Acceptance and Use of Technology (UTAUT) model to examine the relationship between the UTAUT constructs and the behavioural intention of employees to adopt intelligent applications in a South African ICT organisation. The model was extended to include General Awareness, Attitude and Trust, job classification, employment contract type, and education level as moderating variables to examine the influence on behavioural intention. The cross-sectional study included the collection of empirical data through an anonymous online survey. Respondents were also given the opportunity to respond to open-ended questions (divergent question technique) on barriers and enablers to new technology adoption. The analysis results revealed that performance expectancy and effort expectancy are not significant predictors of adoption. Social influence is a weak predictor of adoption. General Awareness, Attitude and Trust, and facilitating conditions were strong predictors of the behavioural intention to adopt intelligent applications. Key outcome topics are insufficient training, management support and strategy, financial constraints, and data management. The results of this study contribute to the body of knowledge on extended factors of UTAUT on influencing the adoption of intelligent applications in the ICT Sector. The study also provides insights to ICT leaders, talent managers, and technology service providers on factors that support the adoption of intelligent applications.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Intelligent Applications; Artificial Intelligence; Transformation; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth